Pesantren in the Changing Indonesian Context: History and Current Developments - M. Falikul Isbah (P3M STAIN Kudus, 2020)
This article discusses the history of pesantren as an educational institution in the changing Indonesian context, and provides a snapshot on their current development and enrolment trends. It aims to provide an updated comprehension on Indonesian pesantren, which is an important aspect in understanding the contemporary development of Islam in Indonesia. The data presented here is based on systematic review of existing literature and policy documents, interviews with key policy makers, and observation in some pesantren. I argue that Indonesian pesantren have continued to grow over different historical periods due to their adaptability in the changing contexts. Such adaptability is seen in their adoption of modern schooling system, their incorporation of non-religious subjects into their curricula, as well as their dynamic integration into the national education system.